2016
DOI: 10.1088/2053-1583/3/1/015008
|View full text |Cite
|
Sign up to set email alerts
|

Electron-hole asymmetry in the electron-phonon coupling in top-gated phosphorene transistor

Abstract: Using in-situ Raman scattering from phosphorene channel in an electrochemically topgated field effect transistor, we show that its phonons with A g symmetry depend much more strongly on concentration of electrons than that of holes, while the phonons with B g symmetry are insensitive to doping. With first-principles theoretical analysis, we show that the observed electon-hole asymmetry arises from the radically different constitution of its conduction and valence bands involving π and σ bonding states respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 47 publications
(96 reference statements)
2
29
1
Order By: Relevance
“…Jing et al [9] based on DFT calculations, report that TCNE withdraws 0.40 electrons from phosphorene while TTF donates 0.15 electrons. These resultsd iffer from the report of Chakraborty et al [10] who examined Ramans cattering of phosphorene in an electrochemically top-gated field effect transistor.T hese workers find that the Raman A g phonons are more affected by electrons than holes. Furthermore, the B g band was insensitive to electrochemical doping.…”
supporting
confidence: 73%
“…Jing et al [9] based on DFT calculations, report that TCNE withdraws 0.40 electrons from phosphorene while TTF donates 0.15 electrons. These resultsd iffer from the report of Chakraborty et al [10] who examined Ramans cattering of phosphorene in an electrochemically top-gated field effect transistor.T hese workers find that the Raman A g phonons are more affected by electrons than holes. Furthermore, the B g band was insensitive to electrochemical doping.…”
supporting
confidence: 73%
“…As suggested by a recent work, the absence of a shift in frequencies as well as full-widths at half-maximum (see Figure S2.1) rules out any n-type doping in the antidot lattice but is inconclusive toward the presence of p-type doping. 83 Furthermore, this result indicates the structure is likely free of any strain since stretching- and compression-induced Raman frequency shifts up to 11 cm −1 /(% strain) are expected in both phosphorene and few-layer BP. 84,85 We also note that across samples the Ag1:Ag2 intensity ratio ( i.e ., the ratio of peak heights) remains between 0.5 and 0.6 from pristine to antidot regions, excluding the likelihood of thinning or oxidation due to atmospheric exposure or patterning.…”
Section: Resultsmentioning
confidence: 82%
“…It is an elemental semiconductor with direct band gap of ∼0.3 eV. Recently there is revival of interest in BP from the prospective of a layered material which allows us to study the exciting properties of a mono and few layers of BP [1][2][3][4][5][6][7][8] . It is found that the band gap depends on the thickness of its film: 0.3eV for thickness > 4nm and 1.2 eV for single layer thick BP 9 .…”
Section: Introductionmentioning
confidence: 99%